Current differences in dental education between Chinese and Western models. (24th June 2016) - Wang, Y. H.; Zhao, Q.; Tan, Z.
Abstract: Dental education is the foundation of a country's development of dental science. Economic conditions and cultural backgrounds vary across countries; hence, there are some differences in dental education between Chinese and Western models, including the education programmes, licensures, curricula, teaching methods, facilities. These differences may become obstacles for mutual communication and the development of dental education. In the last 5 years, China has introduced several policies and published some standards, such as the residency programmes and Accreditation Standards for Undergraduate Dental Education Programs. These actions aim to improve the current situation of dental education and reduce the gap between Chinese and Western education models. Indeed, some changes have been made. This article provides a brief introduction of the existing differences and changes and can, thus, serve as a reference for educators.